Daylight Performance in an Austrohungarian Heritage Building - Biljana Antunović; Miroslav Malinović; Jelena Rašović; Stefan Petrović (AGG+, 2020)
The aim of this paper is to investigate the daylight performance in an Austro-Hungarian heritage building located in Banja Luka, Bosnia and Herzegovina. The building was originally used as a military headquarters and was later reused for administration and educational functions. The measurement of daylight was performed in a representative room-office in the building. The measurement results are discussed with respect to international standards and in relation to the specific architecture of the building. Furthermore, the simulation of the daylight performance was performed by using the Design Builder software.